Evaluasi manajemen pengadaan dan distribusi obat di dinas kesehatan kota Bandar Lampung periode tahun 2016 - Nopiyansyah Nopiyansyah; Anny Victor Purba; Wahyudi Uun Hidayat (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Evaluation of drug management on procurement and distribution at Bandar Lampung Health Authority Background : Management of public medicine and medical supplies in aimstoen sure continuity, availability and affordability of efficient drug services, availability and affordability of efficient drug services. Procurementis a continuous activity starting from selection, determining the amount needed, adjusting between demand and budget, selecting procurement methods, selecting suppliers, determining contract specifications, monitoring procurement and payment processes.Purpose : To determine the mechanism of drug procurement, drug distribution and delivery problems, constraints faced in the procurement and distribution of drugs.Method: A qualitative descriptive with technique of collecting data through in-depth interviews and reviews of documents on drug procurement and distribution.Results: Procurement of drug scarried out by the Pharmacy Installation of the Bandar Lampung Health Authority based on usage pattern was not in accordance with the report on the use of the drug request sheets that have been prepared by the Public health centers. There were 78 drug items (44.3%) held more than those proposed, 77 drug items (43.7%) drugs were heldless than proposed, and only 21 medicinal items (12%) drugs that were carried out according to the ones proposed. Based on the results of the interview, problems with the distribution and delivery of drugs sent by the Pharmacy Installation founded problems which were 30 of Public health centers of drug has been sent expire date <1 year, 7 health centers have been sent expired date drugs and 26 health centers have been sent drugs that were not ordered. The most common constraints faced in the procurement and distribution of drugs carried out are not availabe drugs in pharmaceutical whole sales and drugs sent to the Public health centers not in accor dance with tho serequested by the Public health centers.Conclusion : The procurement of drugs carried out and usage pattern is not in accordance with the report on the use of the drug request sheet that has been prepared successfully, ABC VEN method according to budget, the comordibity method was not appropriate wheres drugs most of which were held clinically not in accordance with the 10 most common diseases that occurred in the Bandar Lampung Health Authority in 2016.Keywords: Drugs management; Procurement; Distribution; Pharmacy installationPendahuluan: Manajemen obat publik dan perbekalan kesehatan di bertujuan untuk menjamin kelangsungan, ketersediaan dan keterjangkauan pelayanan obat yang efisien, efektif dan rasional serta menjamin kualitas mutu obat. Pengadaan merupakan kegiatan yang berkesinambungan dimulai dari pemilihan, penentuan jumlah yang dibutuhkan, penyesuaian antara kebutuhan dan dana, pemilihan metode pengadaan, pemilihan pemasok, penentuan spesifikasi kontrak, pemantauan proses pengadaan dan pembayaran.Tujuan: Untuk mengetahui mekanisme pengadaan obat, masalah pendistribusian dan pengiriman obat, kendala yang dihadapi dalam pengadaan dan pendistribusian obat.Metode: Penelitian deskriptif kualitatif dengan pengumpulan data melalui wawancara mendalam dan telaah dokumen pengadaan dan pendistribusian obat.Hasil: Pengadaan obat yang dilakukan Instalasi Farmasi Dinas Kesehatan Kota Bandar Lampung berdasarkan pola konsumsi tidak sesuai dengan laporan pemakaian lembar permintaan obat yang telah disusun puskesmas. Terdapat 78 item obat (44,3%) yang diadakan lebih dari yang diusulkan, 77 item obat (43,7%) yang diadakan kurang dari yang diusulkan, dan hanya 21 item obat (12%) yang diadakan sesuai dengan yang diusulkan. Berdasarkan hasil wawancara, masalah pendistribusian dan pengiriman obat yang dikirimkan oleh Instalasi Farmasi Dinas Kesehatan Kota Bandar Lampung yakni 30 puskesmas pernah dikirimkan obat expiredate < 1 Tahun, 7 Puskesmas pernah dikirimkan obat yang sudah expiredate dan 26 puskesmas pernah dikirimkan obat yang tidak dipesan. Kendala yang paling sering dihadapi dalam pengadaan dan pendistribusian obat yang dilakukan oleh Instalasi Farmasi Dinas Kesehatan Kota Bandar Lampung yaitu obat kosong di pedagang besar farmasi dan obat yang dikirimkan ke puskesmas tidak sesuai dengan yang diminta oleh puskesmas.Simpulan: Pengadaan obat yang dilakukan Instalasi Farmasi Dinas Kesehatan Kota Bandar Lampung berdasarkan pola konsumsi tidak sesuai dengan laporan pemakaian lembar permintaan obat yang telah disusun puksesmas, metode ABC VEN sesuai anggaran, metode komordibitas belum sesuai dimana obat yang terbanyak diadakan secara klinis tidak sesuai dengan 10 penyakit terbanyak yang terjadi.